2017
DOI: 10.5194/amt-2017-237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional uncertainty of GOSAT XCO<sub>2</sub> retrievals in China: Quantification and attribution

Abstract: Abstract. The regional uncertainty of XCO 2 (column-averaged dry air mole fraction of CO 2 ) retrieved using different 14 algorithms from the Greenhouse gases Observing SATellite (GOSAT) and its attribution are still not well understood. This 15 paper investigates the regional performance of XCO 2 within a band of 37°N~ 42°N segmented into 8 cells in a grid of 5° 16 from west to east (80°E ~120°E) in China, where there are typical land surface types and geographic conditions. The former 17 include the various … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…From Figure 8 a, it can be found that the dXCO 2 in western area, the desert area of Xinjiang, shows high values even if there are much less anthropogenic emission over this area as shown in Figure 4 b. This is likely resulted in the uncertainty of ACOS XCO 2 retrievals in desert which has been indicated by Bie et al [ 34 ].…”
Section: Resultsmentioning
confidence: 73%
“…From Figure 8 a, it can be found that the dXCO 2 in western area, the desert area of Xinjiang, shows high values even if there are much less anthropogenic emission over this area as shown in Figure 4 b. This is likely resulted in the uncertainty of ACOS XCO 2 retrievals in desert which has been indicated by Bie et al [ 34 ].…”
Section: Resultsmentioning
confidence: 73%